A highly flexible inorganic framework with amphiphilic amine assemblies as templates. Issue 2 (30th November 2016) - Huang, Hui-Lin; Lin, Hsin-Yau; Chen, Pei-Shan; Lee, Jey-Jau; Kung, Hui-Chen; Wang, Sue-Lein
Abstract : An inorganic framework with 24-and-30-ring stacked channels showed extreme flexibility, with a volume change of up to 27.1% under pressure without undergoing a phase transformation. Abstract : A zinc phosphite–phosphate framework, (HA)2 [Zn3 (HPO3 )4− x (HPO4 ) x ] (1 ; A = cha, coa, iba, pa, and ha ; x = 0.3–1) with nanometer-scale channels was prepared. The framework exhibited an extraordinarily high flexibility, 13% expansion at ambient pressure and 27% contraction under a high pressure of over 2.3 GPa without undergoing any phase transformation. The volume changes in the compression–decompression process are reversible. Such unusual adaptability is rare in pure inorganic networks. The molecular volumes of templates range from 165 Å 3 to 228 Å 3, which allows to vary channel aperture increasingly from 13.02 to 15.34 Å. Remarkably, three types of organic amine template assemblies, captured in inorganic frameworks, were identified in this study. Presented herein is the first example that demonstrates a successfully controlled template assembly that helps to obtain a flexible inorganic framework with nanosized pores in a systematic manner.